Stroke Survivors’ Preference of Herbal Center to Hospital - Florence O. Okoro; Chidinma O. Nwoha; Nkeiru C. Ogoko; Emmanuel C. Nwoha; Chibundu C. Amadi; Peace N. Nwoha; Ifeoma H. Okpara; Nnenna Chinagozi-Amanze; Catherine Wali; Ebere Dike; Polycarp U. Nwoha (International Journal of Complementary Medicine, 2021)
Proceeding to hospital immediately stroke occurs is important for early intervention that would minimize the consequences of stroke. But most stroke patients in developing countries prefer herbal centers than hospital. Reasons for this attitude have not been established. Two well-trained assistants were used to interview 117 stroke survivors who attended Bebe Herbal Center (BHC) in Nigeria for at least two visits. The survivors self-reported their experiences in hospitals visited and at BHC. Data obtained were analyzed using Independent t-test, Pearson’s chi-squared test, on SPSS package version 23. Significant value was set at p<0.05. Results showed the survivors comprised 48.7% males and 51.3% females, with mean age 63.98±10.41 years (range: 40-84 years). Following onset of stroke, 61.5% went firstly to hospital, 21.4% to traditional healing places, and 17.1% to BHC. Eventually all survivors went to BHC and 99.1% said they were satisfied with treatment received at BHC. Seventy-nine (68.1%) said they experienced substantial recovery under one month, 25.9% between 1-6 months. All the survivors who went firstly to hospitals said they received inadequate care in them. None of the hospitals they visited had CT or MRI equipment. Pearson’s chi-squared test showed that the impact of stroke had a significant difference between males and females regarding checking of blood pressure after stroke (χ2=7.62; df=3; P<0.05). The inadequate care received in hospitals and the early satisfactory recovery in BHC influence stroke patients in Nigeria to reject going to hospital.
Keywords: hospital